TALK-WRITE: A GROUNDBREAKING TECHNIQUE FOR SHAPING THE STUDENTS’ ARGUMENTATIVE WRITING SKILLS ON DISCUSSION ESSAYS - Soni Tantan Tandiana; Fuad Abdullah; U Komara (Institut Pendidikan Indonesia Garut, 2018)
AbstractSince argumentative writing skills play an indispensable role in higher educational contexts, the students are required to produce academic works representing their academic insights and critical perspectives towards problematized issues around them. Conversely, the students may frequently encounter intricacies while applying complicated syntactic forms and proper aspects during writing Discussion essays as one of the argumentative writing genres. For this reason, the current study aimed at exploring how Talk-Write technique facilitates the students in writing Discussion essays. This study involved 30 EFL students and an experienced writing teacher at a university in Indonesia. The data were analyzed through thematic analysis following the notions of Talk-Write (Meyers, 1985; Ling, 1986; Radcliffe: Crasnich & Lumbelli, 2005). The findings indicated that Talk-Write technique enables the students to produce the Discussion essays. Besides, it stimulated them to speak actively in English while negotiating ideas, exchanging debatable arguments and positioning stance and voice. Briefly, Talk-Write technique can facilitate the students in exchanging vocal to scribal dialogue, gaining pivotal and desired ideas and fostering professional competencies as the talkers and the writers and personal styles.Keywords: Talk-Write technique, Discussion essays, Argumentative writing skills